2013
DOI: 10.1177/1352458513512707
|View full text |Cite
|
Sign up to set email alerts
|

Genetic burden of common variants in progressive and bout-onset multiple sclerosis

Abstract: Our results suggest that the liability of disease is better captured by common genetic variants in BOMS than PrMS cases. The absence of inflammatory activity and male gender further raise the difference between clinical courses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…This is in agreement with previous studies based on a smaller number of risk loci in which no difference in MS risk was observed between BOMS and PPMS patients, 2,7-10 except for a difference between these disease course groups in male patients only in one study. 10 Our findings also correspond to what is seen in family studies, where it was shown that affected family members do not necessarily have the same clinical course, 22 but do present with similar genetic risk scores. 7,8 A pathological hallmark of MS is intrathecal IgG synthesis, which can be measured in a qualitative (OCB status) or quantitative (IgG index) way.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with previous studies based on a smaller number of risk loci in which no difference in MS risk was observed between BOMS and PPMS patients, 2,7-10 except for a difference between these disease course groups in male patients only in one study. 10 Our findings also correspond to what is seen in family studies, where it was shown that affected family members do not necessarily have the same clinical course, 22 but do present with similar genetic risk scores. 7,8 A pathological hallmark of MS is intrathecal IgG synthesis, which can be measured in a qualitative (OCB status) or quantitative (IgG index) way.…”
Section: Discussionsupporting
confidence: 93%
“…Quality controls were performed as described elsewhere. 5 , 12 Whenever a specific SNP was absent in one of the arrays, the best available proxy according to HapMap release 24 was considered for the analyses; in this case, the r 2 value between the original and proxy SNP was included in the wGRS calculation. The score was also calculated after the exclusion of the HLA polymorphism in order to evaluate the contribution of non-HLA risk variants (wGRS–non-HLA).…”
Section: Methodsmentioning
confidence: 99%
“…. Notably, no study has been able to identify consistently a significant difference in genetic burden or variants between relapsing and progressive‐onset MS …”
Section: Cause Versus Course – Are the Risk Factors Different?mentioning
confidence: 99%